1984
DOI: 10.1002/ajh.2830170403
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of chronic lymphocytic leukemia cells after in vitro treatment with epstein‐barr virus or phorbol ester. I. Immunologic and morphologic studies

Abstract: Leukemic cells from ten patients with "nonsecretory," B-type chronic lymphocytic leukemia (CLL) were cultured alone or in the presence of Epstein-Barr virus (EBV) or a phorbol ester (12-0-tetradecanoylphorbol-13-acetate; TPA) for 7 days. At periodic intervals the cell morphology, cytoplasmic immunoglobulin content (direct immunofluorescence) and capacity for immunoglobulin secretion (hemolytic plaque assay) were assessed. A variable but significant number of the TPA-treated CLL cells from all patients expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…These suggestions are strengthened by the fact that normal and malignant B cells can only be 'immortalized' and grown as continuous B lymphoblastoid or B leukaemia/lymphoma cell lines after infection with Epstein-Barr virus (EBV). On the other hand, it was found that EBV induced phenotypic changes in B-CLL cells similar to those seen after TPA-treatment (Deegan & Maeda, 1984).…”
Section: Isoenzyme Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…These suggestions are strengthened by the fact that normal and malignant B cells can only be 'immortalized' and grown as continuous B lymphoblastoid or B leukaemia/lymphoma cell lines after infection with Epstein-Barr virus (EBV). On the other hand, it was found that EBV induced phenotypic changes in B-CLL cells similar to those seen after TPA-treatment (Deegan & Maeda, 1984).…”
Section: Isoenzyme Analysismentioning
confidence: 76%
“…The phorbolester 12-0-tetradecanoylphorbol 13-acetate (TPA) could induce the differentiation of B-CLL cells in vitro (Toetterman et al, 1980). Several investigators have found morphological, functional, cytochemical and immunological changes in B-CLL cells caused by treatment with TPA (Gordon et al, 1984;Dufer & Bernard, 1984;Toetterman et al, 1981a,b;Deegan & Maeda, 1984).…”
mentioning
confidence: 99%
“…The close interrelationship is further demonstrated by the possibility of transforming CLL cells in vitro into cells that display all the characteristics of IC and PLL (34)(35)(36)(37)(38). Some activated CLL cells changes phenotype into immunoblasts.…”
Section: Pat Hophysiological Considerationsmentioning
confidence: 96%
“…Epstein-Barr virus (EBV) is only capable of stimulating B CLL cells to proliferate and secrete monoclonal immunoglobulin in short-term culture [8], and difficulty has been encountered in establishing immortalized cell lines from B Correspondence: Dr Hanne V. Marquart, Institute of Medical Biology. Department of Medical Microbiology, Odense University.…”
Section: Introductionmentioning
confidence: 99%
“…B CLL CD5 ' cells are capable of producing autoantibody in vitro [6] but show lack of humoral response to foreign antigens [7]. Epstein-Barr virus (EBV) is only capable of stimulating B CLL cells to proliferate and secrete monoclonal immunoglobulin in short-term culture [8], and difficulty has been encountered in establishing immortalized cell lines from B Correspondence: Dr Hanne V. Marquart CLL cells [9]. This difficulty may be explained by the fact that CLL cells express only low numbers of CR2 which functions as the receptor for EBV (reviewed in [10]).…”
Section: Introductionmentioning
confidence: 99%